Clinical and Anatomic Complexity of Patients Undergoing Coronary Intervention With and Without On-Site Surgical Capabilities: Insights From the Veterans Affairs Clinical Assessment, Reporting and Tracking (CART) Program. (January 2021) - Waldo, Stephen W.; Hebbe, Annika; Grunwald, Gary K.; Doll, Jacob A.; Schofield, Richard
Abstract : Background: Professional society consensus statements articulate the clinical and anatomic complexity of patients that may undergo percutaneous coronary intervention (PCI) without on-site cardiothoracic surgery, although compliance with these recommendations has not been assessed. We sought to evaluate the clinical and anatomic complexity of patients undergoing PCI with and without cardiothoracic surgery on-site. Methods: We identified all patients undergoing PCI in the Veterans Affairs health care system between October 2009 and September 2017. The clinical and anatomic complexity of patients treated at sites with or without cardiothoracic surgery was evaluated with a comparative interrupted time series, and mortality was ascertained in a propensity-matched cohort. Results: We identified 75 564 patients who underwent PCI, with the majority (53 708, 71%) treated at sites with cardiothoracic surgery. The overall clinical complexity was statistically greater for those treated at sites with cardiothoracic surgery (National Cardiovascular Data Registries CathPCI: 18.4) compared with those at sites without (17.8, P <0.001) throughout the study, with similar annual increases in complexity before (2% versus 3%; P =0.107) and after (3% versus 3%; P =0.704) January 2014. The anatomic complexity of patients treated was also statistically greater (Veterans Affairs SYNTAX: 11.0 versus 10.2; P <0.001) and increased at comparable rates (2% versus 1%, P =0.731) before 2014. After publication of the consensus statement, anatomic complexity declined at sites with cardiothoracic surgery (−2%) but increased at sites without on-site surgery (5%, P =0.025) such that it was similar at the end of the study ( P =0.622). Referrals for emergent cardiothoracic surgery were rare regardless of treatment venue (61, 0.08%) and the hazard for mortality was similar (hazard ratio, 0.883 [95% CI, 0.662–1.176]) after propensity matching. Conclusions: There are minor differences in complexity of patients undergoing coronary intervention at sites with and without cardiothoracic surgery. Clinical outcomes are similar regardless of treatment venue, suggesting an opportunity to improve access to complex interventional care without sacrificing quality. Abstract : Supplemental Digital Content is available in the text.